Toward standardization of care: The feeding readiness assessment after congenital cardiac surgery. (17th November 2017) - Ehrmann, Daniel E.; Mulvahill, Matthew; Harendt, Shaunda; Church, Jessica; Stimmler, Amy; Vichayavilas, Piyagarnt; Batz, Sanja; Rodgers, Jennifer; DiMaria, Michael; Jaggers, James; Barrett, Cindy; Kaufman, Jon
Abstract: Background: Feeding practices after neonatal and congenital heart surgery are complicated and variable, which may be associated with prolonged hospitalization length of stay (LOS). Systematic assessment of feeding skills after cardiac surgery may earlier identify those likely to have protracted feeding difficulties, which may promote standardization of care. Methods: Neonates and infants ≤3 months old admitted for their first cardiac surgery were retrospectively identified during a 1‐year period at a single center. A systematic feeding readiness assessment (FRA) was utilized to score infant feeding skills. FRA scores were assigned immediately prior to surgery and 1, 2, and 3 weeks after surgery. FRA scores were analyzed individually and in combination as predictors of gastrostomy tube (GT) placement prior to hospital discharge by logistic regression. Results: Eighty‐six patients met inclusion criteria and 69 patients had complete data to be included in the final model. The mean age of admit was five days and 51% were male. Forty‐six percent had single ventricle physiology. Twenty‐nine (42%) underwent GT placement. The model containing both immediate presurgical and 1‐week postoperative FRA scores was of highest utility in predicting discharge with GT (intercept odds = 10.9, P  = .0002; sensitivity 69%, specificity 93%, AUC 0.913). The false positive rate was 7.5%. Conclusions: In this analysis, systematic and standardized measurements of feeding readiness employed immediately before and one week after congenital cardiac surgery predicted need for GT placement prior to hospital discharge. The FRA score may be used to risk stratify patients based on likelihood of prolonged feeding difficulties, which may further improve standardization of care.